Advanced Patterns in Distributed Event-Driven Architecture: Multi-Channel Communication and Workflow Orchestration for High-Volume Enterprise Systems - Makarand Gujarathi (International Journal of Computational and Experimental Science and Engineering, 2026)
Event-driven architecture is a common architectural pattern for solving problems in enterprise systems that need to be responsive, scalable, and effective at handling live streaming feeds of events across distributed system nodes. This article describes architectural patterns to solve the most critical problems in multi-channel WebSocket systems, subscription-based event filtering, stateful workflow orchestration, and resource-constrained state replication. Multi-channel WebSocket architectures allow events of different types to be emitted on separate channels, leading to more flexible application control over data flow and independent scaling. By providing filtering at the server side, subscription-based filtering methods invert the broadcast model, potentially improving battery and bandwidth consumption. Lightweight state management patterns enable the processing of high-frequency events with low computational and memory costs. Business Process Management integration patterns enable resilient orchestration of complex and long-running multi-step processes through durable state persistence and compensation transactions. Retriable connection management patterns include graceful reconnection, exponential backoff, and explicit state synchronization as strategies to handle network disconnections. They have been shown to improve battery life, state management, and short- and long-term uptime benefits when implemented in production systems serving millions of concurrent users and connected devices.